Eco-Friendly Synthesis of MgO Nanoparticles and Their Antibacterial Performance - Sapna Chandel (International Journal of Advance in Molecular Engineering, 2025)
Nanoparticles (<100 nm in size) due to their enhanced surface area and high chemical reactivity have been a boon, ranging from micro to macro level. This has increased its applicability in various fields such as Food, textile, environment, biomedicine etc. Various metal oxides have been employed in Biomedical applications for their antibacterial, antioxidant and anticancerous activities. But MgO NPs have received much attention due to their high stability, non-toxicity and low cost. Because MgO NPs produce reactive oxygen species (ROS) and zone of inhibition (ZOI), they are thought to have exceptional antibacterial action against both gram-positive and gram-negative bacteria. They can be easily synthesized by various methods such as sol gel, hydrothermal, precipitation, green synthesis, microwave assisted, micro emulsion, oxidation and sonochemical methods. Out of these, the most economical method is green synthesis of MgO NPs and is currently discussed here.
Keywords: Magnesium oxide nanoparticles; antibacterial activity; biomedical applications; green synthesis; reactive oxygen species